Transformational Innovation In The Creative And Cultural Industries - Rieple, Alison; DeFillippi, Bob; Schreiber, David (New York Routledge, 2023)
"There has been increasing scholarly interest in the management of creative and cultural industries (CCIs) as both economically and socially significant sectors. However, Transformational Innovation in the Creative and Cultural Industries uniquely focuses on how innovation in these industries transforms industry practice. This textbook uncovers the strategic role of innovation for organizations in the creative and cultural sector, with practical guidance to help understand the seismic disruptions brought about by the recent global health crisis. The authors examine how innovation in business models, products, services, and technology has disrupted the competitive landscapes of the arts world. Innovations are characterized as deriving from other industries as well as via exogenous shocks that privilege some companies over others. Case studies bring to life how innovation is used strategically in different ways around varying competitive forces now. This book provides readers with both the conceptual tools and industry examples to understand how innovation can be a productive tool for transforming their own creative and cultural industry practice and performance during a period of rapid technological change and unprecedented societal challenge. This makes the book an ideal resource for students and practitioners in all creative and cultural industry sectors"--
Includes bibliographical references and index.
Keywords: Cultural Industries; Cultural Industries; Cultural industries